2019
DOI: 10.3389/fnmol.2019.00291
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Level of PKMζ Underlies the Excessive Anxiety in an Autism Model

Abstract: Anxiety affects the life quality of a significant percentage of autism patients. To understand the possible biological basis of this high anxiety level, we used a valproic acid (VPA) model of autism. Anxiety level is significantly higher in VPA-injected mice, at both P35 and P70. In addition, protein kinase Mζ (PKMζ) level in the basolateral amygdala (BLA) is significantly higher in VPA mice at both ages. Consistent with this finding, infusion of a PKMζ-blocking peptide z-pseudosubstrate inhibitory peptide (ZI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…Data with AMN082 would suggest the use of mGluR7 receptor agonists for treating anxiety (Spooren et al, 2010;Cieślik et al, 2018). Anxiety level is significantly higher in VPA-injected and BTBR mice (Gao et al, 2019;Queen et al, 2020). In agreement with previous results, we found overexpression of mGluR7 alleviates their anxiety-like traits.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Data with AMN082 would suggest the use of mGluR7 receptor agonists for treating anxiety (Spooren et al, 2010;Cieślik et al, 2018). Anxiety level is significantly higher in VPA-injected and BTBR mice (Gao et al, 2019;Queen et al, 2020). In agreement with previous results, we found overexpression of mGluR7 alleviates their anxiety-like traits.…”
Section: Discussionsupporting
confidence: 91%
“…Stereotype and behavior rigidity are widely known as core and defining features of ASD (Gilbert and O'Connor, 2020). Many lines of evidence have shown that VPA-treated and BTBR mice exhibited the increase in marble burying (Amodeo et al, 2012(Amodeo et al, , 2014Baronio et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Western Blot. As our previously described ( Gao et al, 2019 ), tissues were collected, homogenized in RIPA buffer (Beyotime Biotechnology, China) containing 1 mM PMSF (Sigma), 25 μM leupeptin (Sigma), and 1 μg/ml aprotinin (Sigma), and centrifuged at 4°C for 0.5 h at 10,000 g, with the supernatant collected. Total protein lysates made from hippocampus or entire brain were mixed with SDS gel-loading buffer and heated for 5 min at 100°C.…”
Section: Methodsmentioning
confidence: 99%
“…ICR mice were housed and fed at Peking University Shenzhen Graduate School as our previous study did (Gao et al, 2019). All experiments have been approved by the Peking University Shenzhen Graduate School Animal Care and Use Committee and were performed following the ARRIVE guidelines on the Care and Use of Experimental Animals.…”
Section: Animalsmentioning
confidence: 99%
“…Brain tissue processing was performed based on previously published methods (Donato et al, 2015;Gao et al, 2019). In brief, upon removal, whole brains were fixed overnight in 4% paraformaldehyde at 4 • C, followed by cryoprotection with 30% sucrose for 48 h. Brains were then paraffin-embedded and sectioned at 40 µm on a cryostat (Leica CM1860 UV, Germany).…”
Section: Brain Tissue Processing and Immunostainingmentioning
confidence: 99%